Evaluation of α-Glucosidase Inhibitor Activity of Ethanol Extract of Soursop Leaf (Annona muricata L.) - Nursamsiar; Anjas Kila; Fitriyanti Jumaetri Sami (PT CENDEKIA SCIENCE AND TECHNOLOGY, 2025)
Soursop (Annona muricata L.) is a plant widely used in traditional medicine, where people typically consume soursop leaf infusions or supplements to help regulate blood sugar levels. This plant contains several bioactive compounds, including flavonoids, quercetin, tannins, alkaloids, fatty acids, phytosterols, morinol alcohol, and annonol. Among these, flavonoids, quercetin, and tannins are suspected to have antidiabetic properties. In recent years, interest has increased in the potential of natural products, especially plant extracts, as alternative therapeutic agents for managing diabetes, particularly through the inhibition of α-glucosidase, an enzyme involved in carbohydrate digestion and glucose absorption. Despite the widespread use of soursop, there is limited scientific evidence evaluating its α-glucosidase inhibitory activity. This research aims to assess the potential of ethanol extract of soursop leaves (Annona muricata L.) as an α-glucosidase inhibitor using a microplate reader. In this study, the inhibition of α-glucosidase was determined by the enzymatic reaction between α-glucosidase and the substrate p-nitrophenyl-α-D-glucopyranoside (PNPG), measured spectrophotometrically using a microplate reader. The results of the study indicate that the ethanol extract of soursop leaves exhibited moderate inhibition of α-glucosidase, with an IC50 value of 764.14 µg/mL. While the extract demonstrated some inhibitory potential, it was less potent compared to standard α-glucosidase inhibitors. These findings suggest that although the ethanol extract of soursop leaves has α-glucosidase inhibitory activity, it may require further optimization or combination with other compounds to enhance its effectiveness. This research contributes to the growing body of evidence regarding the antidiabetic properties of soursop and provides insights into its potential as a functional food or herbal supplement for managing diabetes.